Hypoxia in Kidney Disease - Maarten Koeners (Frontiers Research Topics, 2018)
Kidney disease is a complex health problem, often coinciding with cardiovascular pathology (e.g. hypertension) and metabolic disturbances (e.g. obesity and diabetes). It is also a disturbingly fast growing global public health problem, e.g. chronic kidney disease affects an estimated ~9-16% of the population. Besides the public health issues this results in a large economic burden as kidney diseases contributes disproportionally to about a quarter of total health care costs. Experimental and clinical data solidly support the view that kidney tissue hypoxia plays a critical and intricate role during the genesis and progression of both chronic and acute kidney diseases. This research field is currently at the very beginning of integrating pre-clinical with clinical research in which hypoxia related mechanism are quantified by non-invasive imaging. In combination with the fact that some key questions remain unanswered, this offers exciting new research perspectives that are waiting to be explored. With this Research Topic we aim to discuss and find answers to the following research question: 1) What are the temporal relationships between hypoxia and kidney disease? 2) Can we demonstration causation between hypoxia and kidney disease? 3) Can renal hypoxia be considered as a treatment target in kidney disease? 4) Can hypoxia (e.g. in the urine) be considered a biomarker of kidney disease? 5) Does hypoxia ramp-up sympathetic activity? 6) Does hypoxia trigger inflammation? 7) Is hypoxia caused by changes in sodium reabsorption and/or mitochondrial function? 8) Which molecular mechanisms are involved in hypoxia in kidney disease? 9) Which gene expressions change due to hypoxia in kidney disease? 10) Can we generate new and translational insights using non-invasive imaging technologies? Our overall aim is identify the mediators/controllers of hypoxia in kidney disease. If we understand more about the sequence of events leading to hypoxia, its regulation and consequences in renal disease, we might be able to have a major impact in clinical practice. I.e. more accurate and earlier diagnosis, novel treatment targets, and novel therapies.